Evaluation of dry eye-associated symptoms and signs after microincision cataract surgery - Ozyol, Pelin; Ozyol, Erhan (The European Research Journal, 2016)
Objectives. To evaluate the effects of microincision cataract surgery on dry eye-associated symptoms and signs. Methods. This prospective study included 40 eyes of 32 patients. Microincision cataract surgery was performed to eyes through 2.2 mm superior clear corneal incision. Dry eye-associated symptom scoring, corneal sensitivity test, Schirmer 1 test, tear break-up time (tBUT) were measured at 3 days before and 3 days, 10 days, 1 month, 3 months after surgery. ‘One way ANOVA for repeated measures’, and Pearson correlation tests were used for statistical analysis. Results. The postoperative symptom scores were significantly different from preoperative value at all consecutive examinations (p<0.01). The decrease in superior corneal sensitivity was significant at 3 and 10 days (p<0.001), and recovery to preoperative level had occured at 1 month. The decrease in tBUT was significant up to 1 month (p=0.007 for 3 days, p=0.008 for 10 days, and p=0.018 for 1 month). The difference in Schirmer 1 test between pre- and postoperative each visit was not significant (p=0.32, p=0.12, p=0.092 and p=0.088; respectively). Symptom score was highly correlated with operative time (r=0.72, p<0.01), and there was an inverse correlation between operative time and postoperative mean tBUT values (r=-0.52, p<0.01). Conclusions. Despite microincision cataract surgery, an aggravation of dry-eye associated symptoms, and temporary dry eye-associated signs might develop. Operative time and exposure to operating microscope light seem to an important factor on symptoms and tear film stability.